Expanding (2p^2)^3 without Exponents
This problem involves simplifying an expression with exponents. Let's break it down step-by-step:
Understanding the problem:
- (2p^2)^3: This expression means we're multiplying the base (2p^2) by itself three times.
Applying the rules of exponents:
- (ab)^n = a^n * b^n: We distribute the exponent outside the parentheses to each factor inside.
- (a^m)^n = a^(m*n): When raising a power to another power, we multiply the exponents.
Step-by-step solution:
- Apply the first rule: (2p^2)^3 = 2^3 * (p^2)^3
- Apply the second rule: 2^3 * (p^2)^3 = 8 * p^(2*3)
- Simplify: 8 * p^(2*3) = 8 * p^6
Therefore, (2p^2)^3 expanded without exponents is 8 * p^6.